2021
DOI: 10.5194/acp-2021-615
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Marine gas-phase sulfur emissions during an induced phytoplankton bloom

Abstract: Abstract. The oxidation of dimethyl sulfide (DMS; CH3SCH3), emitted from the surface ocean, contributes to the formation of Aitken mode particles and their growth to cloud condensation nuclei (CCN) sizes in remote marine environments. It is not clear whether other, less commonly measured marine-derived, sulfur-containing gases share similar dynamics to DMS and contribute to secondary marine aerosol formation. Here, we present measurements of gas-phase volatile organosulfur molecules taken with a Vocus proton t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…However, this result highlights that biological activity can drive variations in dissolved ratios of DMS and MeSH resulting in variability in ambient FDMS:FMeSH emission ratios, and that further study is needed to elucidate this mechanism and its spatiotemporal variability. Measurements during an induced mesocosm phytoplankton bloom experiment using seawater collected as SIO pier immediately before this study showed that the ratio of gas phase DMS to MeSH varied by more than a factor of five over the course of a phytoplankton bloom and decay (Kilgour et al, 2021). DMS to MeSH ratios 350 in that study were strongly linked to changes in bacterial sulfur demand and changes in the available pool of dissolved sulfur…”
Section: Dms and Mesh Emission Fluxmentioning
confidence: 65%
See 3 more Smart Citations
“…However, this result highlights that biological activity can drive variations in dissolved ratios of DMS and MeSH resulting in variability in ambient FDMS:FMeSH emission ratios, and that further study is needed to elucidate this mechanism and its spatiotemporal variability. Measurements during an induced mesocosm phytoplankton bloom experiment using seawater collected as SIO pier immediately before this study showed that the ratio of gas phase DMS to MeSH varied by more than a factor of five over the course of a phytoplankton bloom and decay (Kilgour et al, 2021). DMS to MeSH ratios 350 in that study were strongly linked to changes in bacterial sulfur demand and changes in the available pool of dissolved sulfur…”
Section: Dms and Mesh Emission Fluxmentioning
confidence: 65%
“…Heterogeneous chemistry of the DMS oxidation product HPMTF is not included in our base model case. HPMTF 415 heterogeneous chemistry has been proposed to be a potentially large sink for HPMTF which would reduce SO2 production from DMS (Novak et al, 2021;Veres et al, 2020;Vermeuel et al, 2020). These details of HPMTF heterogeneous chemistry do not impact the yield of SO2 from MeSH described previously but do impact the calculated relative production of SO2 from MeSH compared to DMS.…”
Section: Impact Of Mesh On Marine Sulfur Dioxide Production 390mentioning
confidence: 94%
See 2 more Smart Citations
“…Marine dimethyl sulfide (DMS: CH3SCH3) accounts for >50% of natural gas-phase sulfur emissions (Chin et al, 1996;Andreae, 1990;Kilgour et al, 2021). Once emitted into the troposphere, oxidation of DMS takes place within 1-2 days, forming other sulfur-containing products such as sulfuric acid (H2SO4) and methane sulfonic acid (MSA: CH3SO3H) (Boucher et al, 2003;Breider et al, 2010).…”
Section: Introductionmentioning
confidence: 99%